The Gendered World of Trespassing Tokens: A Glimpse - Datta, Shivani; Bhardwaj, Gopa (Epistemik Press, 2024)
The present research work intended to study the effect of Gender, Occupational gender type and proportional numerical strength on the experience of Workplace Tokenism. According to Tokenism theory (Kanter, 1977), “Tokens” (those who comprise less than 15% of a group’s total) are expected to experience a variety of hardships in the workplace, such as feelings of Heightened Visibility, Isolation, and limited opportunities for advancement. Most previous studies have defined Tokenism narrowly in terms of proportional numerical strength at workplace. The present study extends the framework of prior research work by examining the experience of Workplace Tokenism as a function of Gender, Occupational Gender Typing (Gender Atypical/Gender Neutral or Non Atypical) and Proportional (Male-Female) Numerical Strength at workplace (Tokens/Non Tokens), with an examination of different groups of Males and Females in Gender Atypical and Gender Neutral/Non Atypical occupations as numerical Tokens and Non Tokens respectively. Total sample size was 40. Results depict a complex interaction of Gender, Gender type of Occupation and Male Female proportional numerical strength on the experienced Tokenism.